(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2018)
Vladimir Maximov, one of the most eminent representatives of the “third wave” of Russian emigration and the publisher and editor-in-chief of the Kontinent magazine for many years, in his prose works presented a concept of the truth as a value in the totalitarian USSR reality. Maximov’s mission, as a writer and the editor of the emigration magazine, was the criticism of communistic ideology that was based on a lie – opposite of truth. The mean of truth is a word. Writers and journalists are assigned to take high responsibility for truth. It is not a secret that under totalitarian regime there was strict censorship. In the memorable times of Pravda and Izvestiya the unreal coverage faking truth dominated. Written words became the most important tool for the Communist Party propaganda. In Farewell from Nowhere the author portraited the community of journalists and writers. He described the mechanisms and rules, on which basis the press operated in a totalitarian country. Vladimir Maximov was exiled from the country due to standing up for truth, and his works were not published in Russia until the communism fall.